Early-Life Socioeconomic Circumstances and Physical Activity in Older Age: Women Pay the Price. (February 2022) - Chalabaev, Aïna; Sieber, Stefan; Sander, David; Cullati, Stéphane; Maltagliati, Silvio; Sarrazin, Philippe; Boisgontier, Matthieu P.; Cheval, Boris
Health in older age is shaped by early-life socioeconomic circumstances (SECs) and sex. However, whether and why these factors interact is unclear. We examined a cultural explanation of this interaction by distinguishing cultural and material aspects of SECs in the context of physical activity—a major determinant of health. We used data from 56, 331 adults between 50 and 96 years old from the Survey of Health, Ageing and Retirement in Europe (SHARE), a 13-year, large-scale, population-based cohort. Confounder-adjusted logistic linear mixed-effects models showed an association between the cultural aspects of early-life SEC disadvantage and physical activity among women, but it was not consistently observed in men. Furthermore, these associations were compensated for only partially by adult-life socioeconomic trajectories. The material aspects of early-life SECs were not associated with adult-life physical activity. These findings highlight the need to distinguish different aspects of SECs because they may relate to health behaviors in diverse ways.